Differential gene expression of immunity and inflammation genes in colorectal cancer using targeted RNA sequencing - Holubekova, Veronika; Loderer, Dusan; Grendar, Marian; Mikolajcik, Peter; Kolkova, Zuzana; Turyova, Eva; Kudelova, Eva; Kalman, Michal; Marcinek, Juraj; Miklusica, Juraj; Laca, Ludovit; Lasabova, Zora (Frontiers in Oncology, 2023)
Introduction: Colorectal cancer (CRC) is a heterogeneous disease caused by molecular changes, as driver mutations, gene methylations etc., and influenced by tumor microenvironment (TME) pervaded with immune cells with both pro-tumor and anti-tumor effects. The studying of interactions between the immune system (IS) and the TME is important for developing effective immunotherapeutic strategies for CRC. In our study, we focused on the analysis of expression profiles of inflammatory and immune-relevant genes to identify aberrant signaling pathways included in carcinogenesis, metastatic potential of tumors as well as association of Kirsten rat sarcoma virus (KRAS) gene mutation. Methods: A total of 91 patients were enrolled in the study. Using NGS, differential gene expression analysis of 11 tumor samples and 11 matching non-tumor controls was carried out by applying a targeted RNA panel for inflammation and immunity genes containing 475 target genes. The obtained data were evaluated by the CLC Genomics Workbench, and R library. The significantly differentially expressed genes (DEGs) were analyzed in Reactome GSA software and some selected DEGs were used for real-time PCR validation. Results: After prioritization, the most significant differences in gene expression were shown by the genes TNFRSF4, IRF7, IL6R, NR3CI, EIF2AK2, MIF, CCL5, TNFSF10, CCL20, CXCL11, RIPK2 and BLNK. Validation analyzes on 91 samples showed a correlation between RNAseq data and qPCR for TNFSF10, RIPK2 and BLNK gene expression. The top differently regulated signaling pathways between the studied groups (cancer vs. control, metastatic vs. primary CRC and KRAS positive and belong to immune system, signal transduction, disease, gene expression, DNA repair and programmed cell death. Conclusions: Analyzed data suggest the changes at more levels of CRC carcinogenesis, including surface receptors of epithelial or immune cells, its signal transduction pathways, programmed cell death modifications, alterations in DNA repair machinery and cell cycle control leading to uncontrolled proliferation. This study indicates only basic molecular pathways that enabled the formation of metastatic cancer stem cells and may contribute to clarifying the function of the IS in the TME of CRC. A precise identification of signaling pathways responsible for CRC may help in 46 selection of personalized pharmacological treatment.